Intersections of endocrine pathways and the epithelial mesenchymal transition in endometrial cancer - Gelissen, Julia H.; Huang, Gloria S. (Frontiers in Oncology, 2022)
The epithelial mesenchymal transition (EMT) is the process by which cancer cells of epithelial origin, including endometrial cancer, acquire a mesenchymal phenotype with enhanced migratory and invasive capacity, to facilitate metastasis. The regulation of EMT is tissue-specific, and in endometrial cancer, endocrine signaling pathways serve as critical regulators of EMT. The intersections of endocrine signaling and EMT highlight potential avenues for therapeutic intervention to target cancer metastasis with the aim of reduced mortality.